Metodika vyšetřování finanční kriminality - Balciar, Jan (2006)
Financial criminality has far-reaching social and economic consequences on the internal stability of the state. To a large degree it manifests itself as a complex commercial law and criminal law problem the solution of which requires special expertise and constantly renewed know-how not only from those in legislative bodies but also from personnel at relevant state administration and law enforcement authorities.